The Application of Taguchi Experiments in Developing Gecko-Inspired Dry Adhesive for Macro-Handling Applications - Nyanga, L.; Govender, R.A.; Matope, S. (The South African Journal of Industrial Engineering, 2025)
Synthetic dry adhesives have been developed to mimic the gecko’s adhesion using lithography and micro-machining of a mould to cast a suitable elastomer. Previous international studies used nano-manufacturing processes, which are expensive and are not readily available in South Africa. In this study, a simple micro-machining method was used using a three-axis milling machine and Vytaflex 30 to develop an adhesive pad. The Taguchi method to design experiments was used to determine the optimum machining conditions to create micro-wedges. The results show that, although a maximum adhesion pressure of 1,924 Pa was obtained with a preload pressure of 1,323 Pa, the adhesion force produced might not be suitable for macro-handling applications.